Comparison of Determining Oil Reserves in Reservoir Z Based on Volumetric Methods, Material Balance, and Decline Curve Analysis - Azzahra, Baiq Maulida; Rahalintar , Pradini (Journal of Earth Energy Science, Engineering, and Technology, 2024)
This study was conducted at Reservoir Z, an oil well in East Kalimantan, known as one of the largest producers in the area with a production rate of 500 BOPD. Determining the oil reserves in this new production well is crucial, as well as using volumetric and material balance methods to estimate the initial oil in place. The volumetric method calculated an Original Oil in Place (OOIP) of 0.197596.080 MMSTB, while the Material Balance method estimated 0.2075 MMSTB. The 5% difference between the two methods indicates their accuracy in determining OOIP. The study also examines the dominant drive mechanism. Using the Material Balance-Havlena Odeh method with the drive index, it was found that the dominant drive mechanism in Reservoir Z is the Solution Drive, with gas expansion in the oil playing a significant role in pushing oil to the production well. To predict future well performance, the Decline Curve Analysis method was used. The results showed an economically recoverable cumulative production of 130,938.94 STB, and the well can be produced for 3 years and 2 months. The recovery factor at Reservoir Z, indicating the amount of producible oil compared to the initial amount, is 81%. This study provides essential information for managing the oil well in Reservoir Z and understanding its reserve potential better.